2003
DOI: 10.1093/ajcn/77.2.517
|View full text |Cite
|
Sign up to set email alerts
|

Ingested probiotics reduce nasal colonization with pathogenic bacteria (Staphylococcus aureus, Streptococcus pneumoniae, and β-hemolytic streptococci)

Abstract: The results indicate that regular intake of probiotics can reduce PPB in the upper respiratory tract. The results also indicate a linkage of the lymphoid tissue between the gut and the upper respiratory tract.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
112
3
3

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 179 publications
(118 citation statements)
references
References 30 publications
0
112
3
3
Order By: Relevance
“…The choice of the specific probiotic agent used in this study (Lactobacillus rhamnosus GG) also differed from the agent(s) used in existing trials. This agent was chosen because it had the most robust safety data and had cursory data suggesting that it may have preferential activity in the upper airways (37)(38)(39). Given the paucity of comparative data in this area, it remains unknown whether other agents would have similar or superior results.…”
Section: Discussionmentioning
confidence: 99%
“…The choice of the specific probiotic agent used in this study (Lactobacillus rhamnosus GG) also differed from the agent(s) used in existing trials. This agent was chosen because it had the most robust safety data and had cursory data suggesting that it may have preferential activity in the upper airways (37)(38)(39). Given the paucity of comparative data in this area, it remains unknown whether other agents would have similar or superior results.…”
Section: Discussionmentioning
confidence: 99%
“…But local and remote actions of probiotic organisms have been suggested. Some studies have shown a reduction in potentially pathogenic organisms even at sites distant to the gut (vagina and nasal cavity) following oral probiotic therapy (Gluck and Olaf Gebbers, 2003;Reid et al, 2003). One proposed mechanism is that probiotics initiate an immune response in the gut-associated lymphoid tissue, resulting in circulation of primed T and B cells and immune activation at distant mucosal surfaces (Perdigon et al, 1999;.…”
Section: Discussionmentioning
confidence: 99%
“…As obtained a study which looked upon the specific measurement of pathogenic bacteria in human nasal canals, the results showed that those patients who were given the supplemented yogurt experienced a markedly reduced level of nasal colonization of pathogenic bacteria -Staphylococci aureus, Streptococcus pneumonia and β haemolytic streptococci [23].…”
Section: Reduction In Colonization Of Nasal Pathogenic Bacteriamentioning
confidence: 99%